Phochemical behavior of trans-[Ru(NH3)4P(OEt)3L]2+ complex ions (L = P(OEt)3, CO, H2O) - Mazzetto, Selma Elaine; De Almeida Plicas, Lidia Maria [UNESP]; Tfouni, Elia; Franco, Douglas Wagner (American Chemical Society (ACS), 1992)
trans-[Ru(NH3)4P(OEt)3H2O] 2+, trans-[Ru(NH3)4(P(OEt)3)]2+, and trans-[Ru(NH3)4P(OEt)3CO]2+ were photolyzed with light of 313 nm on the lowest energy ligand field excited state. Photoaquation of the thermally substitution inert ammonia is observed for all three complexes with φ ≅ 0.30 mol/einstein. trans-[Ru(NH3)4(P(OEt)3)2] 2+ undergoes P(OEt)3 photoaquation with φ ≅ 0.12 mol/einstein, while trans-[Ru(NH3)4P(OEt)3CO]2+ displays CO photoaquation with φ = 0.07 mol/einstein. The results suggest that the electronic configuration of the lowest energy excited state of these complexes have contributions from E and A2 states. Furthermore, in trans-[Ru(NH3)4P(OEt)3CO]2+ the photoaquation of CO is explained by depopulation of a bonding dπ orbital and population of a σ* orbital. © 1992 American Chemical Society.